PKM Digital Branding Koperasi dan UKM Desa Bangun Purba Timur Jaya - Maradona, Hendri; Yasdomi, Kiki; Febrinova, Rina; Jannah, Wirda Jannatul; Fatmawati, Dinni; Ridho, Muhammad (Journal of Community Engagement Research for Sustainability, 2023)
Bangun purba timur jaya village is one of the villages in Rokan Hulu, Riau Province which has 7 villages or sub-districts with a total size of 150.15 Km2 and is still categorized as Developing Village[1]. The Bangun Purba Timur Jaya Village Cooperative only focuses on savings and loans and has not been able to build more innovative cooperative enterprises, as well as SMEs, almost all existing SMEs are still individuals, making palm sugar to sell to the market or to merchants is one of the main commodities and a source of income for the population in Bangun Purba Timur Jaya Village. Most people are still independent in their business in making palm sugar, and no one has grouped or formed a cooperative. The results of the discussion were that the author found that efforts to develop products towards more high selling value still cannot be realized by the community because there are no village cooperative efforts to maximize individual-based SMEs into joint business groups, which are later expected to be able to independently increase production. The concept of SME promotion and branding that has not been implemented has resulted in a relatively insignificant increase in production[2]. The implementation method consists of four stages, namely product development, graphic design, business website management, and social media content.